Isolation, characterization and identification of extracellular enzyme producer Bacillus licheniformis from municipal wastewater and evaluation of their biodegradability. Issue 1 (January 2018) - Sonune, Nilesh; Garode, Anil
Abstract: In the present investigation, a total of 34 bacterial isolates were isolated from municipal wastewater and sludge samples. Out of 34, 5 isolates were selected based on their growth on wastewater agar medium and were identified on the basis of morphological, cultural and biochemical tests. The enzyme production study showed that all the isolates were able to produce lipase and protease while one isolate (NW1D) showed amylase production. The bioremediation potential of these enzymes producing bacteria was investigated and the results suggest that the isolate NW6 was most efficient for bioremediation and showed reduction in biochemical oxidation demand (BOD), chemical oxidation demand (COD), nitrate and phosphate by 50.65%, 20%, 56.25% and 31.13% respectively after 72 h. Further, the NW6 isolate identified as Bacillus licheniformis by 16S rRNA sequencing and was optimized for different parameters to achieve effective results. The results showed that overall optimum inoculum size, retention time and agitation speed for NW6 were 10% (v/v), 96 h and 200 rpm respectively. The reduction in BOD, COD, nitrate and phosphate was found to be 54.55%, 36%, 24.83% and 26.42% respectively with 10% inoculum size. At 96 h retention time with 10% inoculum, BOD, COD, nitrate and phosphate reduction was 69.16%, 42.5%, 49.89% and 39.62% respectively. The reduction in BOD, COD, nitrate and phosphate was found to be 72.08%, 51%, 51.87% and 31.13% respectively at 200 rpm with 10% inoculum. Further, the NW6 may find application in municipal wastewater treatment to prevent water pollution as well as a potential enzyme production.